اسلامی تعلیمات کی روشنی میں اولڈ ایج ہومز: مغربی تصور، تاریخ اور والدین کی عزت و تکریم کا تجزیہ: Old Age Homes in the Light of Islamic Teachings: Western Concepts, History, and Contemporary Challenges - Batool Zahra; Prof Dr Mustafeez Ahmad Alvi (International Research Journal of Arabic and Islamic Studies, 2024)
In contemporary society, the practice of sending elderly parents to old age homes or evicting them as a burden has become increasingly common. This trend reflects a shift in attitudes where some individuals believe that by placing their parents in such institutions, they are absolved of their caregiving responsibilities. Old age homes are often perceived as necessary facilities, but they inadvertently suggest that the elderly are a burden to their families, highlighting a decline in traditional family structures. This phenomenon contrasts sharply with Islamic teachings, which emphasize the respect, care, and responsibility owed to parents. The Quran and Hadith outline explicit guidelines for honoring and supporting one’s parents, underscoring the familial obligations that transcend modern conveniences or societal pressures. The history of old age homes, particularly in Western contexts, reveals an evolution from almshouses to more structured facilities, driven by changing social and economic conditions. Initially, almshouses provided shelter for the poor and sick, but as societies industrialized and family dynamics shifted, the need for such institutions grew. The contemporary model of old age homes reflects these historical developments but raises significant challenges, including the erosion of familial bonds and the cultural implications of institutionalizing elder care. This paper aims to explore the concept of old age homes from an Islamic perspective, contrasting it with Western practices and historical developments. It seeks to highlight the importance of upholding Islamic principles regarding elder care and address the contemporary challenges faced by both individuals and societies in reconciling these differing approaches.